Monarch butterfly optimization based energy management system for electric vehicle with interleaved landsman converter - C. Milton; T. S. Sivarani (Automatika)
The toxic emissions from combustion engine cars and businesses using fossil fuels have steadily increased over time in today's world of expanding needs and urbanization. Due to some advantages over vehicles with traditional engines, using electric vehicles is the most well-liked and successful alternative. The performance of electric cars is significantly influenced by an energy management system (EMS). In this study, a multifunctional power electronic interface capable of using two sources simultaneously throughout the charging process monarch butterfly optimization (MBO) based EMS for plug-in electric vehicles (PHEV) has been developed. The battery can be charged from the grid or solar photovoltaic (SPV), depending on the need. This study designs an electric vehicle (EV) charging system that uses an interleaved landsman converter followed by a flyback converter. As a result, the suggested converter helps in improving battery safety as well as user safety for the vehicle. The proposed control technique is simulated using system models created with MATLAB/Simulink. The outcomes of the simulation demonstrate that the devised technique offers better control in terms of vehicle stability. A number of simulations are run to evaluate the efficiency and performance of the proposed approach.